ASSESSMENT OF KNOWLEDGE AMONG HEALTH CARE PROVIDERS REGARDING INTRAMUSCULAR INJECTION ADMINISTRATION. - Bp, Srividya; H, Nagabushan; Hs, Drupad (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objectives: The aim was to assess the existing knowledge of intramuscular (IM) injection administration technique among health care providers in teaching hospital. Methods: A cross-sectional study was conducted among medical interns, final year nursing students, and MBBS Phase-II students (health care providers) of Mandya Institute of Medical Sciences, Mandya. A total of 257 health care providers participated in this study and were asked to narrate the steps of IM injection technique. The correctness of technique was graded using a standard checklist of 10 steps. Knowledge was assessed by number of steps answered correctly by them. Results: Out of 257 participants, all the steps of IM injection technique were correctly answered by 18.8% of nursing students, and 17% of medical interns. Knowledge of site selection and sterilization of site for IM injection was good among all the groups (97.7%). Steps involving angle of insertion of needle into the muscle, checking whether needle is correctly inserted into muscle, proper disposal of syringe and sanitization of hand after the procedure was answered correctly by 89.1%, 72.3%, 42.8% and 45.5% of participants respectively. Conclusion: Nursing students and medical interns had better knowledge regarding technique of IM injection when compared to MBBS Phase-II students. However, the knowledge concerning the disposal of syringe and sanitization in the hand was better among nursing students than the other two groups. Even though, medical interns and nursing students have responded well, still there is a scope for further improvement in the procedure. Keywords: Health care providers, Intramuscular injection, Knowledge.